Effect of Coronin-1 on macrophage polarization by regulating the expression of CD14 - FAN Xiaoxia; CHEN Quan; SUN Xuehua; TIAN Ruoyuan (Di-san junyi daxue xuebao, 2021)
Objective To investigate the correlation between Coronin-1 and macrophage polarization and its possible mechanism. Methods Firstly, M1 and M2 RAW246.7 macrophage cells were established, and the expression of Coronin-1 at mRNA and protein level was detected by real-time PCR and Western blotting. Then, over-expressed (Coronin-1 Plus) and knockout (Coronin-1 KO) cell lines were constructed in RAW246.7 cells, and the expression levels of inducible nitric oxide synthase (iNOS) in over-expressed, knockout and normal-expressed Coronin-1 cells were detected by real-time PCR and Western blotting. The interaction and enrichment of Coronin-1 and CD14 related proteins were analyzed by protein-protein interaction (PPI) network and Gene Ontology (GO) enrichment analysis. Real-time PCR and Western blotting were used to detect the expression level of CD14 in over-expressed, knockout and normal Coronin-1 cells, and the expression level of iNOS after treatment with 100 ng/mL LPS. Then, CD14 knockdown cell lines (Control-CD14 KD) and CD14 knockdown Coronin-1 Plus cell lines (Coronin-1 Plus-CD14 KD) were constructed. After treatment with LPS (100 ng/mL), the expression of iNOS was detected by real-time PCR and Western blotting. Results M1 and M2 macrophage models were successfully constructed, and the expression of Coronin-1 in M1 type macrophages was significantly higher than that in the Control group (P < 0.05). The mRNA expression of iNOS was significantly lower in Coronin-1 Plus group than control group (P < 0.01), and the expression of CD14 was obviously higher in Coronin-1 Plus group than Control group (P < 0.05). After LPS treatment, the expression of iNOS in Coronin-1 Plus group was significantly higher than that in Control group (P < 0.01). There was no significant difference in iNOS level of the LPS treated Control-CD14 KD and Coronin-1 Plus-CD14 KD groups with the Control group (P>0.05). Conclusion The M1 polarization of macrophages leads to higher expression of Coronin-1, but the over-expression of Coronin-1 does not directly lead to the M1 polarization of macrophages. Its over-expression can lead to up-regulation of CD14 expression, and Coronin-1 can promote LPS-induced macrophages to M1 type polarization through the CD14 pathway.